Entenda RP: campanha de difusão da profissão de Relações Públicas - Meimaridis, Rebecca [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The profession of public relations presents itself in Brazil currently as a profession in expansion. However, by it’s time of performance, it should already be instated and legitimatized by society like other areas that even though appeared later, are already known and understood. Therefore, this project intends to seek for answers about the current situation, analyzing since it’s appearance in Brazil until now a days. With this analysis of the whole historic trajectory it is possible to understand the many movements that occur today in the area of public relations that are constantly searching for a legitimating and valued profession. However in this context surfaces a paradox: How to value something that is not known? So this project starts up again a campaign of divulgation of public relations promoted by the ABRP (Brazilian Association of Public Relations), now on the internet using the social networks, seeking to have a wider audience, interaction and reach. By this campaign it is possible to show to different publics the existence and relevance of the profession in the Brazilian context in objective and practice way making it more comprehensible in Brazil

A profissão de Relações Públicas se apresenta atualmente no Brasil como uma profissão em expansão. No entanto, pelo seu tempo de atuação, ela já deveria estar instaurada e legitimada pela sociedade como outras áreas que mesmo surgindo depois, já são conhecidas e entendidas pela sociedade. Desta forma, este trabalho pretende buscar respostas sobre a atual situação, analisando desde sua inserção no Brasil até os dias atuais. Com um análise de toda a sua trajetória histórica é possível entender vários movimentos que acontecem hoje na área de relações públicas que buscam uma constante legitimação e valorização da área. Porém surge neste contexto um paradoxo: como valorizar algo que não é conhecido? Assim este trabalho retoma uma campanha de divulgação das relações públicas promovida pela ABRP em 1982, agora na internet, por meio das redes sociais, visando dar maior divulgação, interação e alcance. Por meio da campanha é possível mostrar para diferentes públicos a existência e relevância da profissão no contexto brasileiro de forma objetiva e prática, tornando-a mais compreensível no Brasil
Keywords: Relações publicas - História; Redes sociais on-line; Profissional de relações publicas - Brasil; Propaganda; Public relations; History; Online social networks; Advertising